The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/lt.24691
|View full text |Cite
|
Sign up to set email alerts
|

Differential profile of activated regulatory T cell subsets and microRNAs in tolerant liver transplant recipients

Abstract: Regulatory T cells (Tregs) play a potential role in operational tolerance in liver transplantation (LT) patients, and microRNAs (miRNAs) are known to be involved in immunological responses and tolerance. Thus, we analyzed the implication of different peripheral blood Treg subsets and miRNAs on LT tolerance in 24 tolerant (Tol) and 23 non-tolerant (non-Tol) LT recipients by cellular, genetic, and epigenetic approximation. Non-Tol patients had a lower demethylation rate of the forkhead box P3 (FOXP3) regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…MiRNAs can target mRNAs that regulate production of the DNA methyltransferases, and failures in enzyme production can limit DNA methylation and alter gene activity . Cytokine pathways that direct the differentiation and proliferation of lymphocytes are regulated in part by the miRNAs and homeostatic mechanisms that suppress immune reactivity and tumour formation may also be affected by these gene‐silencing molecules (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs can target mRNAs that regulate production of the DNA methyltransferases, and failures in enzyme production can limit DNA methylation and alter gene activity . Cytokine pathways that direct the differentiation and proliferation of lymphocytes are regulated in part by the miRNAs and homeostatic mechanisms that suppress immune reactivity and tumour formation may also be affected by these gene‐silencing molecules (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Histone modifications are influenced by enzymes including the histone deacetylases (HDCAs), histone acetyltransferases (HATs), histone methyltransferases (HMTs), histone demethylases and the PAD enzyme family [69,83,[85][86][87][88]. MiRNAs can be manipulated by antisense oligonucleotides that inactivate mRNA before translation to miRNAs [226,227] and by epigenetic modifications of methylation-sensitive genes that express the miRNAs [109,110,131,132]. All elements have been manipulated in experimental models of immune-mediated and malignant diseases [33,43,70,126,228,229].…”
Section: Key Elementsmentioning
confidence: 99%
“…Hence, the plasma levels of miR-155-5p and miR-181a-5p after LT potentially help identify patients for IS minimization. Revilla-Nuin et al have reported a set of differentially expressed miRNAs in tolerant recipients after liver transplantation that might promote and control the activation of Tregs necessary to develop operational tolerance (141). Their study showed that miR95, miR24, miR31, miR146a, and miR155 were expressed more in tolerant than in non-tolerant recipients, and were positively correlated with activated Treg markers.…”
Section: Mirnas As Biomarkersmentioning
confidence: 99%
“…These 2 issues are linked by Revilla‐Nuin et al in this issue . Using a cohort of liver transplant recipients who had previously been enrolled in immunosuppression withdrawal trials, the authors compared blood samples from patients who had experienced rejection during withdrawal and had thus been restarted on baseline immunosuppression nontolerant (non‐Tol) compared with those who had been successfully weaned from immunosuppression tolerant (Tol) without experiencing rejection for more than 1 year after withdrawal.…”
mentioning
confidence: 99%
“…Without FOXP3 staining or Treg‐suppressive functional testing, these cells must be viewed as a somewhat mixed T cell population . This perspective is key to interpreting the 3 main results of this study that compared Tregs and microRNAs (miRNAs) in 24 Tol and 23 non‐Tol liver transplant recipients …”
mentioning
confidence: 99%